PENGARUH TAX AMNESTY TERHADAP PROFITABILITAS PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ali Akil Parlindungan Siregar; Noer Azam Achsani; Hendro Sasongko (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Tax amnesty policy in Indonesia has an impact on companies listed on the Capital Market. Companies that take advantage of tax amnesty can be identified from the increase in net assets and equity. This increase results in an increase or decrease in profitability and may affect investors' interest in investing. This research aimed to analyze the influence of tax amnesty and internal and external factors on the company's profitability. This study's samples are companies listed on the main board of the Indonesia Stock Exchange between 2013 and 2018. Panel data regression was used in this study to analyze the data. The result showed that tax amnesty had a significant negative effect on profitability. Internal factors that had a significant positive effect on profitability were current ratio and total asset turnover, while debt to equity ratio negatively affected profitability. External factors that had a significant positive effect on profitability were interest rates and rupiah exchange rates. Tax amnesty negatively affected profitability resulting in corporate profits declining dramatically during the tax amnesty program. Based on the results, it could be concluded that several factors could affect profitability, such as tax amnesty policy, internal factors, and external factors of the company. Keywords: external factors, internal factors, panel data regression, profitability, tax amnesty